2004
DOI: 10.1016/s0378-1097(04)00076-x
|View full text |Cite
|
Sign up to set email alerts
|

Which morphological forms of the fungusAureobasidium pullulansare responsible for pullulan production?

Abstract: Attempts were made to clarify the precise location and possible site of production of the K-glucan pullulan in different morphological forms of the fungus Aureobasidium pullulans. Gold-conjugated pullulanase was used as the specific probe for this purpose. No cell wall pullulan-like material was detected by transmission electron microscopy (TEM) in any morphological form of this fungus, although intracellular electron transparent material bound this probe. When silver enhancement of this gold-conjugated pullul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 13 publications
2
23
0
6
Order By: Relevance
“…With NH 4 + as N source, EPS yields were markedly affected in an airlift reactor by the aeration rate applied (Roukas and Mantzouidou, 2001). They were optimal at 2 vvm, where the population was predominantly mycelia, which might question the widely accepted causal relationship between pullulan synthesis and unicellular forms of this fungus (Campbell et al, 2004;Simon et al, 1993). However, as with many similar studies, the EPS quantified in this work was assumed to be solely pullulan, yet no experimental evidence was presented to support the claim.…”
Section: The α-Glucan Pullulanmentioning
confidence: 70%
See 1 more Smart Citation
“…With NH 4 + as N source, EPS yields were markedly affected in an airlift reactor by the aeration rate applied (Roukas and Mantzouidou, 2001). They were optimal at 2 vvm, where the population was predominantly mycelia, which might question the widely accepted causal relationship between pullulan synthesis and unicellular forms of this fungus (Campbell et al, 2004;Simon et al, 1993). However, as with many similar studies, the EPS quantified in this work was assumed to be solely pullulan, yet no experimental evidence was presented to support the claim.…”
Section: The α-Glucan Pullulanmentioning
confidence: 70%
“…It seems clear (Gibbs and Seviour, 1996a) that NO 3 − favours production of unicells while mycelial growth occurs predominantly with NH 4 + . Enough direct and indirect evidence exists to support the view that pullulan production is restricted to unicellular swollen cells and chlamydospores (Campbell et al, 2004;Simon et al, 1993), while mycelial forms of this polymorphic fungus probably synthesize other EPS material (e.g. Orr et al, 2009).…”
Section: The α-Glucan Pullulanmentioning
confidence: 98%
“…Yeast cells are mainly responsible for pullulan production (1). Till date most of the studies have been reported on mesophilic strain of this fungus which produces pullulan up to level of 30-36 g/l in flask shake experiments or in fermentor experiments at a temperature range of 24-32 o C at different physico-chemical conditions (4,7,8,9,11,13,15,17).…”
Section: Introductionmentioning
confidence: 99%
“…Different strains of A. pullulans produce substantially different titers and yields (on sugar substrates) of pullulan (Campbell et al, 2004;Gibson and Coughlin, 2002;West and Strohfus, 2001). Compared to the other strain, the NRRL Y-2311-1 produced a higher yield of unpigmented and reasonably higher molecular weight pullulan when cultivated under the conditions reported herein.…”
Section: Discussionmentioning
confidence: 99%